Explanation: Given: Remove common term: => Therefore: => ”alt=”-6x^4″ />” /> (Option B) 2. Answer: Option (D) Explanation: Given: Take the common term( s ) out :=> Hence: => (Option D) 3. Answer: Option (B) quadratic trinomial Explanation: Given: The standard form of the polynomial function must have the highest power value first, then second highest, etc. => => (Option B) 4. Answer: Option (C) Explanation: To find the total number of Common and Endler guppies, you need to add the polynomials of the guppies Common and Endler, as follows: Common Guppies: Endler’s Guppies: ( add both)—————————————————————–Total number: ————— ———————————————— So the answer is option (C) 5. Answer: Option (D) Explanation: Let’s first find the total area of the yard: Area total yard = 14x * 19x = Now circular fountain area: Circular fountain area = Ê tre, r = 6xSo, Circular fountain area = Now the final yard area would be: Final yard area = Total yard area – Circular fountain area Final yard area = – => Final yard area = – => Final yard area = the final court = (Option D) 6 Years: Option (A) Explanation: First we will find the total area of the field: Total area of the field= 6x * 10x = Now the area of the stadium: Area of the stadium = 1x * 4x = Now the final lot area would be: End of lot area = Total lot area – These are the final lot stage area = – => End of lot area = (Option A) -i

3x^2+2x-6-(x+5)=3x^2+2x-6-x-5=3x^2+x-11 Second option: 3x^2 + x − 11 will be a polynomial 2) Which of the following shows that the polynomials are closed by subtraction when the polynomial 3×2 + 4 is subtracted from x2+ 2x + 5? x^2+2x+5-(3x^2+4)=x^2+2x+5-3x^2-4=-2x^2+2x+1 Third option −2x^2 + 2x + 1 will be a polynomial

Answer 6

1. Walkthrough B:

option (b) is correct. we obtain a polynomial Step by step procedure: Let: Polynomial 5x -6 and . We have to choose from the given options, which shows that the polynomials are closed by subtraction when the polynomial 5x − 6 is subtracted from . First, we subtract the polynomial as terms are terms with the same variables with the same degree. Here -6x and -5x are similar and 2 and 6 are similar. By adding terms like the ones we get, Polynomial is an algebraic expression that can involve variables with non-negative integer terms and constants. Thus, we get a polynomial. Therefore, option (b) is correct.

3x+3 is my calculated answer!

Answer 7

option (b) is correct. we obtain a polynomial Step by step procedure: Let: Polynomial 5x -6 and . We have to choose from the given options, which shows that the polynomials are closed by subtraction when the polynomial 5x − 6 is subtracted from . First, we subtract the polynomial as terms are terms with the same variables with the same degree. Here -6x and -5x are similar and 2 and 6 are similar. By adding terms like the ones we get, Polynomial is an algebraic expression that can involve variables with non-negative integer terms and constants. Thus, we get a polynomial. Therefore, option (b) is correct.

1. 4x⁶ + 6x⁵ + 8x⁴ is your answer, so b. 2. x^2 − 49 is your answer, so b. 3. 2x^2 + 6x-20 is your answer, so a. 4. (f • g)(2) = 12, the distance in miles traveled by the bike, so b. (but not 100% sure) 5. 8x³-34x²+25x-3 is your answer, so c. 6. 30x^2 – 26x -12 is the polynomial is the answer, so c. 7. not sure: ( 8. not sure: ( 9. not sure: ( 10. x^2 − 14x + 49 is the answer, so a. I hope so! : )

The resulting polynomial contains a maximum of mn positive terms. Walkthrough: Given that one polynomial contains m non-zero terms and the second polynomial contains n non-zero terms. Show after multiplication and combination of similar terms how many positive terms contain the two polynomials. Now, m=1=(a), n=2=(x,y) after multiplying a(x+y)=ax+ay, 2 positive terms. m=2=(a,b), n= 3 =(x,y,z) after multiplying (a,b)(x+y+z)=ax+ay+az+bx+by+bz, 6 positive terms.m=3=(a,b, c ) , n=4=(x,y,z,t) after multiplication (a+b+c)(x+y+z)=ax+ay+az+at+bx+by+bz+bt+ cx +cy+ cz+ct, 12 positive terms. Therefore, we see that after multiplying n positive terms, there are mn positive terms. To prove it, we have to apply mathematical induction. Let therefore be the statement true for m=pen=q number of positive terms, hence mn=pq. We have to show that a vobe statement is valid for m+1, n+1. Considering, (m+1)(n+1)=mn+m+n+1=pq+p+q+1=p(q+1)+1(q+1)=(p+1)( q+1) Therefore, the above statement is true for m+1 and n+1. Thus, there will be mn nonzero terms after multiplication and combination of positive terms.

Answer 6

1. Walkthrough B:

Latest posts by Answer Prime (see all)